Extraction of anthocyanins from Butterfly pea (Clitoria ternatea L. Flowers) in Southern Vietnam: Response surface modeling for optimization of the operation conditions - Pham, Tri Nhut; Chinh Nguyen, Duy; Duc Lam, Tri; Thinh, Pham Van; Le, Xuan Tien; Vo, Dai-Viet N.; Vu, Quang Hieu; Nguyen, Trinh Duy; Bach, Long Giang (Institute of Physics Publishing, 2019)
In this paper, the Response Surface Methodology (RSM), in conjunction with Central Composite Design (CCD), was used to optimize the extraction of anthocyanins from Butterfly pea (Clitoria ternatea L.Flowers) cultivated in Southern Vietnam. The effect of extraction temperatures of solvent ethanol (50-70 °C), duration of extraction (40-50 min) and solid-liquid ratios (20:1-30:1) was measured as independent variables on the total extraction anthocyanins in the response function. The highest anthocyanin content of 132.756 mg/L of butterfly pea anthocyanin was collected at the solid liquid ratio of 23:1, extraction time of 46 min, and temperature 60.6°C. Butterfly pea anthocyanins yield detailed significant correlation with high F values, low P values (<0.0001), and desirable determination coefficient (R2 = 0.9994).